Synthesis, Characterization And Catalytic Study Of Microporous Silicoaluminophosphates In The Esterification Of Levulinic Acid With Ethanol - Ma, Yik Ken (2022)
Silicoaluminophosphate (SAPO-n) number 34 (SAPO-34) and number 35 (SAPO-35) are eight-membered small pore zeolites commonly used as catalysts in the petrochemical industry. However, the time-dependent formation study of these zeolites is rarely studied and their syntheses generally require long crystallization time (at least 24 h) due to the use of organic aminic structural directing agents (SDAs). This project focuses on the hydrothermal synthesis and time-dependent evolution of SAPO-34 and SAPO-35 using a novel 1-propylpyridinium hydroxide ([PPy]OH) SDA. The microscopic and spectroscopic investigations reveal that induction and nucleation precede the formation of fully crystalline SAPO-34 at 200 oC for 19 h which partially transformed into SAPO-36 at 30 h, while pure SAPO-35 (200 oC, 21 h) was obtained from the intrazeolite transformation from SAPO-34. Notably, the [PPy]OH-templated SAPO-34 and SAPO-35 show higher porosity, silicon content and acidity compared to other templating systems. The crystallized SAPO-34 and SAPO-35 were also used to catalyze the esterification of levulinic acid and ethanol under non-microwave instant heating method. The SAPO-34 and SAPO-35 show 93.4% and 96.3% LA conversion, respectively, with 100% selectivity to ethyl levulinate at 190 oC and 20 min. The catalysts also show excellent reusability for at least five cycles and are potential alternatives to the traditional homogenous acid catalysts in the esterification reaction.